1995
DOI: 10.1091/mbc.6.9.1111
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for phosphorylation of cyclin B1 for Xenopus oocyte maturation.

Abstract: Maturation-promoting factor, consisting of cdc2 protein kinase and a regulatory B-type cyclin, is a universal regulator of meiosis and mitosis in eukaryotes. In Xenopus, there are two subtypes of B-type cyclins, designated Bi and B2, both of which are phosphorylated.In this study, we have investigated the biological significance of this phosphorylation for Xenopus cyclin Bi during meiotic maturation. We have used a combination of sitedirected mutagenesis and phosphopeptide-mapping to identify serine residues 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 68 publications
4
76
0
Order By: Relevance
“…In the absence of 4-HT, cyclin B1 accumulated as expected when the cells passed through G 2 and into mitosis ( Figure 6a). Furthermore, a slower migrating form of cyclin B1 was observed after 15 h ( Figure 6a) and most likely reflects cyclin B1 phosphorylation (Li et al, 1995;Hagting et al, 1999). However, activation of DMEKK3:ER* when cells were released from the aphidicolin block prevented the accumulation of cyclin B1 protein which was normally observed after 10 -15 h. Indeed, cyclin B1 levels actually declined to below control levels, and were nearly undetectable 25 h To examine the impact of loss of cyclin A and B on the kinase activities of CDK2 and CDK1, the active complexes were immunoprecipitated using antibodies against cyclin A and cyclin B, and their ability to phosphorylate histone H1 assayed.…”
Section: Activation Of Dmekk3:er* Causes the Loss Of Cyclin A And Cycmentioning
confidence: 96%
“…In the absence of 4-HT, cyclin B1 accumulated as expected when the cells passed through G 2 and into mitosis ( Figure 6a). Furthermore, a slower migrating form of cyclin B1 was observed after 15 h ( Figure 6a) and most likely reflects cyclin B1 phosphorylation (Li et al, 1995;Hagting et al, 1999). However, activation of DMEKK3:ER* when cells were released from the aphidicolin block prevented the accumulation of cyclin B1 protein which was normally observed after 10 -15 h. Indeed, cyclin B1 levels actually declined to below control levels, and were nearly undetectable 25 h To examine the impact of loss of cyclin A and B on the kinase activities of CDK2 and CDK1, the active complexes were immunoprecipitated using antibodies against cyclin A and cyclin B, and their ability to phosphorylate histone H1 assayed.…”
Section: Activation Of Dmekk3:er* Causes the Loss Of Cyclin A And Cycmentioning
confidence: 96%
“…These nuclear-targeted cyclin B1 derivatives contain the five Ser phosphorylation sites in the human CRS domain (S116, S126, S128, S133 and S147) mutated to Ala or Glu, to mimic phosphorylation states of cyclin B1 (Hagting et al, 1999). Xenopus cyclin B1 contains four regulatory phosphoserine sites within the CRS (Li et al, 1995). The expression of NLS-B1 hs-E enhances Gli1 activity to about sixfold over mocktransfected cells (Figure 5b).…”
Section: Expression Of Constitutively Nuclear Cyclin B1 Constructs Enmentioning
confidence: 99%
“…In addition, cyclin B1 is regulated by phosphorylation during G2 phase. Specifically, the cytoplasmic retention signal (CRS) domain of cyclin B1 is phosphorylated on four Ser residues, resulting in nuclear localization of MPF and access to critical nuclear substrates for G2-M progression (Li et al, 1995(Li et al, , 1997Borgne et al, 1999;Hagting et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…By mutagenesis of putative cdc2 kinase and MAP kinase phosphorylation sites in Xenopus, cyclins B1 (Ser-94 and Ser-96) and B2 (Ser-90); Izumi and Maller, (1991) showed that phosphorylation of Xenopus cyclins B1 and B2 is not required for cyclin degradation, induction of mitosis, or induction of oocyte maturation. Intriguingly, another group showed by mutagenesis of Ser-2, 94, 96, 101, and 113 of cyclin B1 that, although cyclin B1 phosphorylation is not required for cdc2 kinase activity, for binding to cdc2 protein, for stability of cyclin B1 before GVBD, or for destruction of cyclin B1 after GVBD or after egg activation, it is required for Xenopus oocyte maturation (Li et al, 1995). Cyclin B1 phosphorylation regulates the biological activity of the Fig.…”
Section: From Prophase To Gvbdmentioning
confidence: 99%